Challenge of the stallions : the legend of Cloud and the wild horses of the Rockies - Kathrens, Ginger, 1946- (The Cloud Foundation and Fox Chapel Publishing, 2023)
"Challenge of the Stallions chronicles the life of the stallion Cloud, leader of a wild horse band in the Rockies' Pryor Mountains. In March of 1994, Emmy Award-winning filmmaker Ginger Kathrens traveled to the Pryor Mountains on the Montana and Wyoming border on a scouting trip for a PBS Wild America program about mustangs. Her observations ignited a lifelong passion for the preservation of wild horses and burros throughout the West. Inside this book, the author recounts her experiences with Cloud, a pale Palomino stallion, and his family over a five-year period, from 2003 to 2008. She captures the beauty and strength of this family and paints an amazing picture that demonstrates the need for these animals to remain wild and free. This remarkable account details Cloud's reign among the wild horse herds in the Rockies, as well as both his immediate family band and rival bands that occupy the same region on the Montana-Wyoming border. Danger abounds in this mountain wilderness, and you'll see the predators, both human and animal, that challenge the stallions' survival, plus the fighting between bands for power, family, and territory. Two powerful stallions, Cloud and Shaman, battle to keep their families together while raising one another's sons. Despite trials of extreme weather, predation on foals by mountain lions, and challenges to his band from up-and-coming bachelor stallions, Cloud prevails. Breathtaking color photography of the wild mustangs and the wildlife who share their Rocky Mountain home gives you an up close and personal look at the feeding, foaling, and freedom of these wild horses, and an interactive QR code grants you access to exclusive and stunning video from its companion PBS Nature documentary series, Cloud: Challenge of the Stallions. Though Cloud went missing in 2018, his legend still lives on in the wild Pryor Mountains. This fascinating book that emphasizes the mission of saving and preserving the wild horse bands in the Rocky Mountains is unlike any other Cloud book available. One-of-a-kind and truly special, Challenge of the Stallions is an absolute must-have for anyone passionate about these stunning wild animals!"--